1997
DOI: 10.1046/j.1468-2982.1997.1701015.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Migraine in Japan

Abstract: This study presents the first nationwide survey of migraine in Japan. A representative sample of 4029 subjects aged 15 years or older was selected from the Japanese population according to the quota method. A combination of telephone interview and mailed questionnaire methods was used. Diagnosis of migraine was based on the International Headache Society (IHS) Classification. The overall prevalence of migraine in the past year was 8.4%; 5.8% was migraine without aura and 2.6% was migraine with aura. Significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
325
20
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(417 citation statements)
references
References 16 publications
43
325
20
2
Order By: Relevance
“…Se considerarmos os casos que preencheram os critérios, com duração da dor menor que 4 horas, essa prevalência sobe para 44,7% (Tabela 2). Questiona-se atualmente a arbitrariedade em se considerar como migranosos apenas aqueles cujas dores duram mais de 4 horas 15 . Por considerarmos que os demais fatores (intensidade, localização e caráter da dor, fenômenos acompanhantes) são tão ou mais importantes que a duração da dor na determinação da diminuição das capacidades, optamos por avaliar ambos os grupos conjuntamente.…”
Section: Discussionunclassified
“…Se considerarmos os casos que preencheram os critérios, com duração da dor menor que 4 horas, essa prevalência sobe para 44,7% (Tabela 2). Questiona-se atualmente a arbitrariedade em se considerar como migranosos apenas aqueles cujas dores duram mais de 4 horas 15 . Por considerarmos que os demais fatores (intensidade, localização e caráter da dor, fenômenos acompanhantes) são tão ou mais importantes que a duração da dor na determinação da diminuição das capacidades, optamos por avaliar ambos os grupos conjuntamente.…”
Section: Discussionunclassified
“…The prevalence of migraine differ according to geography, genetic factors, the ethnic and cultural variations, and socio-cultural structure of the population. Previous population-based studies in female age groups have indicated that the lifetime prevalence of migraine in the European and American populations was higher than those that have been reported from Middle East and Far East countries (Wong et al 1995;Abdul-Jabbar et al 1996;Sakai and Igarashi 1997;Cheung 2000;Takeshima et al 2004) ( …”
Section: Commentsmentioning
confidence: 85%
“…Also, TTH is a typical psychosomatic disease 2) and a high percentage (about 22%) of the general population fulfills the diagnostic criteria of TTH 3,4) . It is necessary for TTH patients to receive the psychosomatic treatment, including the non -pharmacologic therapy, to improve pain -related daily disabilities 5) .…”
Section: Introductionmentioning
confidence: 99%